2010
DOI: 10.1128/jvi.02587-09
|View full text |Cite
|
Sign up to set email alerts
|

A V3 Loop-Dependent gp120 Element Disrupted by CD4 Binding Stabilizes the Human Immunodeficiency Virus Envelope Glycoprotein Trimer

Abstract: Human immunodeficiency virus (HIV-1) entry into cells is mediated by a trimeric complex consisting of noncovalently associated gp120 (exterior) and gp41 (transmembrane) envelope glycoproteins. The binding of gp120 to receptors on the target cell alters the gp120-gp41 relationship and activates the membrane-fusing capacity of gp41. Interaction of gp120 with the primary receptor, CD4, results in the exposure of the gp120 third variable (V3) loop, which contributes to binding the CCR5 or CXCR4 chemokine receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 87 publications
5
79
0
Order By: Relevance
“…Previous studies have suggested that the gp120 V1, V2, and V3 regions (20,23,24) are located at the membrane-distal apex of the Env spike and contribute to the association of gp120 with the trimer (35,36). The flexible fitting of the gp120 core structure in our cryo-EM map demarcates the boundary of the gp120 TAD that comprises the V1, V2, and V3 regions (24).…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies have suggested that the gp120 V1, V2, and V3 regions (20,23,24) are located at the membrane-distal apex of the Env spike and contribute to the association of gp120 with the trimer (35,36). The flexible fitting of the gp120 core structure in our cryo-EM map demarcates the boundary of the gp120 TAD that comprises the V1, V2, and V3 regions (24).…”
Section: Resultsmentioning
confidence: 84%
“…Despite their definition as variable loops, the V2 and V3 regions of gp120 contain highly conserved domains (33). Because several lines of evidence suggest that V3 establishes direct interaction with V2 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and the conserved base of V3 is the binding site for the N-terminal region of the CCR5 coreceptor (34), we looked for potential structural homology between V2 and CCR5. We recognized that the conserved central region of V2 contains two tyrosine residues (Tyr173 and Tyr177) with spacing identical to that of two tyrosines (Tyr10 and Tyr14) present in the N-terminal region of CCR5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite these advances, many critical aspects related to the structural mechanisms of HIV-1 immune vulnerability and evasion remain unresolved. In particular, the fine molecular details of the interaction between the second and third variable loops (V2 and V3, respectively) of gp120, which are believed to play a critical role in stabilizing the prefusion envelope structure (19)(20)(21), are elucidated only partially. Functionally, V2 and V3 cooperate in the formation of quaternary epitopes targeted Significance Despite intensive efforts, the structure of the native HIV-1 envelope trimer-the sole relevant target for vaccine designhas remained elusive.…”
mentioning
confidence: 99%
“…4F, derives from the fact that N295 and N332 occur directly adjacent to the disulfide bond on opposite borders of the V3 loop. This is a critical fulcrum for gp120 function because CD4 weakens V3 constraints on gp41 (19) and induces V3 movement toward the apex of the gp120 trimer (16,17,19) where HIV-1 JRCSF -Ad that had been pretreated for 1 h at 37°C ± 4 μg/mL 2G12. Titers were normalized relative to maximum titers at 100 μM Nt (n = 3, error bars are ± SEM).…”
Section: G12 Inhibits Cd4 and Ccr5 Binding And Blocks A Coreceptordementioning
confidence: 99%
“…After CD4 binding, V3 loop regions of gp120 reduce their constraining hold on gp41 and move toward the trimer apex where they interact with coreceptors, thereby playing a pivotal role in controlling HIV-1 entry rates (16)(17)(18)(19). These and additional conformational changes in gp120 enable gp41 to refold by a multistep process that fuses the viral and cellular membranes.…”
mentioning
confidence: 99%